TATA KELOLA PROGRAM PENANGANAN COVID-19: PERAN DAN KESIAPAN KELURAHAN DALAM MENGHADAPI GELOMBANG PERTAMA COVID-19 - Nikki Prafitri (Fakultas Ilmu Sosial Dan Politik, Universitas Wijayakusuma Purwokerto, 2022)
Governance is a pattern of interaction and program management with the involvement of other parties outside the government. Good governance can be done by implementing important aspects such as participation, accountability, transparency, and responsiveness. The Covid-19 pandemic is a global problem that requires handling from various lines of government, including the urban village as a street-level bureaucracy. The Covid-19 handling program is managed well because it increases Covid-19 cases and carries out major social obligations. The purpose of this study was to determine the governance of the Covid-19 handling program at the village level. The method used is the descriptive qualitative research method. The results showed that the governance of the Covid-19 handling program in the Banjaragung Urban Village was quite good, however, optimizing the success of its governance in managing leadership and the role of the urban village government, synergy between the urban village government and the community in preventing hoax news, assistance in assistance between the urban village government and the community and solid cooperation between the urban village government and the smallest units of government. Keywords: Governance, The Role of the Urban Village Government, Handling Covid-19